Design and optimization of flexible DGS-based microstrip antenna for wearable devices in the Sub-6 GHz range using the nelder-mead simplex algorithm - Gaurav Kumar Soni; Dinesh Yadav; Ashok Kumar; Prince Jain; Manish Varun Yadav (Results in Engineering)
This study introduces a Nelder-Mead Simplex Algorithm based low-profile, flexible, and wearable defected ground structure (DGS)-loaded deformed microstrip antenna for Sub-6 GHz 5 G applications. It is fabricated on a low-loss 20 mil Rogers RT/Duroid 5880 substrate and the antenna demonstrates robust performance with reflection coefficient magnitude (|S11|) of –22.34 dB with peak gain of about 5.57 dBi at resonant frequency (fr) of 2.185 GHz. Comprehensive key performance metrics such as |S11|, far-field gain patterns, and specific absorption rate (SAR) of the proposed antenna is demonstrated. The SAR for 1 g and 10 g tissues at various separation distances are analyzed and presented by utilizing human multilayer phantom model with antenna. Additionally, the lowest SAR is measured to be 0.0959 W/kg for 1 g of tissue and 0.0755 W/kg for 10 g of tissue when the antenna is placed 0.291λ0 away from the model. The study also explores the proposed antenna performance under various bending conditions for the conformability analysis and in different on-body scenarios, with placement on the hand, leg, and chest. The measured |S11| values, particularly strong on the chest, underscore the antenna effectiveness for wearable technology.